Analysis of the implementation of educational hardware based on the Internet of Things (IoT) for the mediation of environmental education experiences: a systematic review (Innovaciones Educativas, 2025)
This research had as objective to analyze the feasibility of the connection between technologies based onInternet of Things (IoT) with the mediation of environmental education practices that contribute to improve scientificcompetencies, technological abilities, and environmental awareness in formal education contexts. A systematic literature review from papers and thesis published in the last 12 years was developed. This process had three stages: 1) identification, 2) screening, and 3) inclusion of the selected studies. Databases such as IEEE Xplore, Science Direct and Scielo were consulted, as well as the search engine Scholar Google. From the inclusion and exclusion process, wereselected a total of 35 publications: 30 papers, two books and three theses. The research results are organized in four subjects: 1) IoT integration in environmental education experimental practices, 2) instrumentation of IoT devices, 3) programming software and tools, and 4) methodological design of environmental education experimental practices. It was shown that the implementation of low-cost educational hardware based on IoT offers the possibility of developing educational experiences which allow students to obtain environmental knowledge through monitoringphysical parameters contextualized to formal learning environments. Besides, it was determined that technologiesemerged from the 4.0 Industry represent an opportunity to impulse educative innovation in science teaching. Themain limitations identified include the availability of research about IoT integration in environmental education, and the methodological diversity among the analyzed studies.
Keywords: climate change; environmental education; experiential method; educational innovation; educational technology